Impact of undesirable outputs on the productivity of US airports - Somchai Pathomsiri (2018)
The paper assesses productivity of 56 US airports during the period 2000-2003. Unlike past work, this study models joint production of both desirable and undesirable outputs (i.e., delays) using the non-parametric directional output distance function. Results are compared to those from models that do not include undesirable outputs. The results show that if delayed flights are excluded from the model, many large but congested airports are found to be efficient. After accounting for delays, small, less congested airports are also found on the efficient frontier. Finally, the model is also used to analyze the effects of other variables. © 2007 Elsevier Ltd. All rights reserved.